Electronic structure, magnetic properties and magnetocaloric performance in rare earths (RE) based RE2BaZnO5 (RE = Gd, Dy, Ho, and Er) compounds. (1st September 2022) - Xu, Peng; Hu, Liang; Zhang, Zhenqian; Wang, Haifeng; Li, Lingwei
Abstract: Nowadays, the rare earths ( RE ) based magnetic materials with various promising functional characterizations are playing particularly important roles in present modern society and daily life. The magnetocaloric (MC) effect which is the basis of solid state magnetic refrigeration (MR) technology has been extensively investigated in various magnetic materials. In this work, a series of high quality RE -based RE 2 BaZnO5 ( RE  = Gd, Dy, Ho, and Er) compounds have been fabricated and a combination of theoretical and experimental investigation has been performed in terms of the crystal structure, electronic structure, magnetic properties and magnetic phase transition (MPT) as well as the MC effects and MC performance. All the RE 2 BaZnO5 compounds are confirmed to crystallize in the orthorhombic structure belonging to Pnma space group and with a typical semi-conductor characteristic. Based on the magnetization measurements and the first principle calculations, all the RE 2 BaZnO5 compounds are ordering magnetically below 3 K and the ground state is of a ferromagnetic (FM) ordering for RE  = Dy or Ho, whereas is of an antiferromagnetic (AFM) ordering for RE  = Gd or Er, respectively. Additionally, considerable MC effects have been observed for all the RE 2 BaZnO5 compounds which are related to the first ordered MPT for RE  = Gd or Er, whereas related to the second order MPT for RE  = Dy or Ho, respectively. Moreover, considerable MC effects and promising MC performance have been realized in the present RE 2 BaZnO5 compounds, especially for the Dy2 BaZnO5 and Ho2 BaZnO5, making them considerable for cryogenic MR applications. Graphical abstract: Image, graphical abstract